The Relationship Between Experiential Learning and Career Outcomes for Alumni of International Development Studies Programs in Canada - Tiessen, Rebecca; Grantham, Kate; Cameron, John (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2018)
In this paper, we explore the relationship between experiential learning and career outcomes for international development studies (IDS) graduates from the perspective of program alumni, by presenting the results of a national survey completed by 1,901 IDS alumni across Canada. Employing study data, we answer the following research questions: (1) What do IDS alumni consider important experiential learning opportunities? and (2) What is the perceived relationship between experiential learning and career outcomes? We argue that documenting IDS graduate perspectives on the relationship between experiential learning and career paths can inform current program opportunities and highlight the relationship between work-integrated learning and career success in this field.